2007
DOI: 10.1063/1.2425026
|View full text |Cite
|
Sign up to set email alerts
|

Volume Fresnel zone plates fabricated by femtosecond laser direct writing

Abstract: In this letter, volume Fresnel zone plates fabricated inside fused silica using femtosecond laser direct writing are demonstrated. A volume zone plate consists of a number of layers of Fresnel zone plates designed to focus light together. Results indicate that volume Fresnel zone plates increase the overall diffraction efficiency significantly. Phase zone plates yield considerably higher diffraction efficiency due to a number of reasons including negligible light absorption, robustness against fabrication phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 8 publications
0
38
1
Order By: Relevance
“…The volume Fresnel zone plate (VFZP) is a focusing device consisting of a number of Fresnel zone plate (FZP) layers inside a transparent medium [1,2]. The FZPs are aligned on the same optical axis and designed to focus light to a single spot as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume Fresnel zone plate (VFZP) is a focusing device consisting of a number of Fresnel zone plate (FZP) layers inside a transparent medium [1,2]. The FZPs are aligned on the same optical axis and designed to focus light to a single spot as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study of VFZP shows that the efficiency of the VFZP continues to increase up to a certain number of FZP layers before it starts to drop [1,2]. Consequently, it is difficult to predict the diffraction efficiency of the VFZP, since light propagation by diffraction through 3D VFZP structures is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Four-level diffractive lenses were shown to provide a maximum efficiency of 56.9% [50]. Srisungsitthisunti et al demonstrated a volume Fresnel zone plate, which consists of a number of layers of Fresnel zone plates designed to focus light together inside fused silica [51].…”
Section: Diffractive Lensesmentioning
confidence: 99%
“…The substantial plasma absorption enables the ablation of materials that are normally difficult to ablate by conventional lasers, such as transparent or low absorption materials [1,2]; and the ablation does not depend on the laser wavelength and material absorption property. Extensive studies utilizing USP laser ablation in basic science and industrial applications have been carried out [3,4]. In recent years, USP lasers have attracted increasing attention in biomedicine, including imaging of early cancers [5,6], human chromosomes dissection [7], and ablation of soft and hard tissues [8][9][10].…”
Section: Introductionmentioning
confidence: 99%